Culturable bacterial abundance in Volvariella volvacea cultivation medium and characterization of its bacteria - Masrukhin Masrukhin; Iwan Saskiawan (Journal of Microbial Systematics and Biotechnology, 2020)
Straw mushroom (Volvariella volvacea) is one of the popular edible fungi in Indonesia. Previous researches showed the correlation among the type of substrate, substrate quality, and its composting process to the microbial community, yield, and biological efficiency. The aim of the research is to analyze the culturable bacteria abundance in straw mushroom cultivation medium, characterize the bacteria in several stages of mushroom cultivation and investigate the interaction between V. volvacea with its resident bacteria. Samples were taken from mushroom farmers in Subang and Karawang regencies, Indonesia. The materials for cultivation medium are the mixture of cotton and paddy straw and the pasteurization was performed at 65-70°C for 7 hours. The result shows the abundance of the bacteria in most of the cultivation stages is relatively similar i.e. 108 CFU/g, except in 15 days after inoculation (DAI), the bacterial abundance is lower i.e.6.24 x 107 CFU/g. Twenty-five isolates were obtained and Gram-positive bacteria is the dominant bacteria found in the cultivation medium, especially rod-shaped Gram-positive bacteria. According to co-culture assay there are nine isolates that decrease the growth rate and clearly inhibit mycelial growth. The other 10 isolates have lower inhibitory activity, and 6 isolates have no inhibitory activity to the mycelial growth. C38 isolates have the highest mycelial growth inhibition. It belongs to rod-shaped Gram positive group of bacteria which isolated from the early stage of V. volvacea cultivation medium (5 DAI).